ANALISIS GAYA HIDUP HEDONIK DENGAN ADANYA PUSAT HIBURAN DAN PERBELANJAAN MODERN BARU DI KOTA KECIL - Eka Adiputra (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2016)
Bojonegoro has become a new oil & gas city, because so many exploration of the although by small & big oil mining company. Corporate Social Responbility from The oil & gas company conducted give more income to society. The increasing of income means more consumption by locale citizens. Thie aim of this research is to analyze the CSR that distributed to Society has used for consumption of life needs or jus for hedonic.